Building of E-Customers’ Loyalty through Image Department Store in Digital Era (Survey of Department Store in the City of Bandung) - Handayani, Rini; Rachmawati, Mariana; Kurniawan, Ryan; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
In the retail sector, the development of the digital era has brought changes to society regarding shopping patterns. The customer loyalty tends to decrease. The purpose of this study was to find out how department store image affects e-customer loyalty and the influence of department store image on e-customer loyalty. The population of this study is customers of online department store shopping sites in Bandung covering Matahari, Metro, Ramayana, and Yogya. The sample customers are department store shopping sites that shop at least once a month at department stores. The analysis used is descriptive and path analysis. The results of the study stated that there was a significant effect of department store image on customer loyalty.